Knowledge of health professionals about occupational accidents in the workplace (Research, Society and Development, 2021)
The hospital work environment is considered unhealthy, as it groups patients with various infectious and contagious diseases and enables many procedures that pose risks of accidents and illnesses for health workers. Given this context, this study aimed to know the knowledge of health professionals about occupational accidents in the workplace. For this, a descriptive, exploratory study with a quantitative approach was carried out. The research was carried out at the General Hospital of the Municipality of Bacabal-MA. A questionnaire containing 19 questions was applied to health professionals who work at the General Hospital of the Municipality of Bacabal-MA, data were submitted to simple percentages. 44 professionals participated, being 33 nursing technicians, 1 pharmacist, 1 social worker and 9 nurses, of which 75% were female, the age among the research participants ranged from 23 to 58 years. The present study showed that most research participants had worked at the institution for less than 10 years, 88.6% said yes, they know what work accidents are, 6.8% know about partial formalities, 38.32% considered work accident that with sharp materials, 45.45% said they had suffered some type of work accident. Therefore, it is noteworthy that training in worker health about the risks, prevention and notification of these injuries are capable of favoring a considerable reduction in the rates of occupational accidents.